Attribution Theory, Bystander Effect and Willingness to Intervene in Intimate Partner Violence - Wijaya, Clara N. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is a crime that is afflicted by a current or previous romantic relationship partner. One in four women has experienced IPV at least once in their lifetime, with physical and psychological consequences. IPV cases tend to go largely unnoticed and under-reported, with low rates of intervention by bystanders. This cross-sectional correlational study investigated whether a combination of attribution theory and the bystander effect could predict the willingness of strangers to intervene in IPV. There were two models tested. The first model examined attitudes towards the victim, while the second one examined attitudes towards the perpetrator. The relationship between perceived responsibility and willingness to intervene was hypothesized to be mediated by sympathy and anger, with the number of bystanders as a moderator to mediating pathways (sympathy towards victim and anger towards perpetrator). A convenience sample of 278 Australian residents aged 18-years and older was presented in a vignette depicting an IPV incident occurring in public. Participants completed measures about the vignette in an online questionnaire. Model testing was conducted using MPlus; confirmatory factor analysis indicated a good fit of the measurement models. After controlling potential covariates, moderated mediation models of victim and perpetrator were analyzed. Attribution theory was a significant predictor in willingness to intervene (f² = .23, p < .001), but the bystander effect was not. Both attitudes towards victim and perpetrator accounted for unique variance in willingness to intervene in IPV, highlighting the importance of examining both. Findings indicate that psychoeducation campaigns aimed at reducing victim-blaming and promoting intervening behavior could be an effective means of preventing IPV.